Development of Knowledge Enrichment Digital Book of Tectonic Earthquake - Serevina, V.; Zahra, S.; Lipikuni, H.F.; Maulana, D. (Department of Physics, Faculty of Mathematics and Natural Sciences, 2023)
This research aims to develop a digital knowledge enrichment book about tectonic earthquakes. Useful for study concepts of waves, elasticity, and Hooke's law. This research method uses the ADDIE (Analysis, Design, Development, Implementation and Evaluation). The validation scores of material experts, learning experts and media experts are in the high category. This digital book has been tested on 49 physics students at San Pedro University, Kupang, Indonesia, and the results are positive. All respondents can enjoy reading this book, increasing their knowledge, and the contents of the book can be understood easily. The test results for this book received a very good assessment in the media aspect, formulating the main problem, revealing facts, choosing arguments logically, and detecting information bias in the book. All respondents were able to draw conclusions from the book and the book was not boring. So, this book can be used as an effective learning resource.